Impact of soot nanoparticle size and quantity on four-ball steel wear characteristics using EDS, XRD and electron microscopy image analysis - Preechar Karin; Pattara Chammana; Pitchaporn Oungpakornkaew; Panyakorn Rungsritanapaisan; Warawut Amornprapa; Chinda Charoenphonphanich; Kobsak Sriprapha (Journal of Materials Research and Technology, 2021)
The effect of soot contamination on the tribological performance of engine oil was investigated. Carbon black is introduced to simplify diesel engine soot contamination. Besides, the tribological performance issue is verified by a four-ball tribometer. The steel ball worn surfaces were studied by Scanning Electron Microscopy (SEM), Optical Microscope (OM) and Energy Dispersive X-ray spectroscopy (EDX). In addition, Transmission Electron Microscopy (TEM) was used to investigate the morphology and nanostructure of soot and carbon black. According to the four ball test results, the average wear scar diameter of steel ball tested with engine oil blended with N220, N330, N550 and N660 by 1% by weight is larger than that of pure engine oil by 26%, 38%, 41%, and 39%, respectively. The wear scar diameter tends to increase after blended larger size of carbon black particle. The steel balls tested with formulated engine oil without soot contamination and with soot contamination by 0.5 wt%, 1 wt%, and 2 wt% have average wear scar diameters of 621, 567, 784 and 894 nm, respectively. On the other hand, wear scar roughness of steel balls tested with formulated engine oil without soot contamination and with soot contamination by 0.5 wt%, 1 wt%, and 2 wt% were 2.28, 0.25, 1.49 and 1.76 μm, respectively. Consequently, quantity of the soot nanoparticle approximately 0.5% by mass in engine oil significantly plays an important role in steel ball wear scar diameter and surface roughness reduction. Moreover, the agglomerated soot which is larger than the oil film thickness might block the lubricant from entering the contact. It leads to the breakdown of the oil film thickness resulting in increasing adhesive wear on the worn surface.
Keywords: Lubricants and Their Additives; Tribology and Wear Analysis; Biodiesel Production and Applications